PROVINCIAL-LEVEL CARDIOVASCULAR AND ALL-CAUSE MORTALITY BURDEN ATTRIBUTABLE TO HYPERTENSION IN CHINA. (April 2021) - Kang, Yuting; Wang, Zengwu; Chen, Zuo; Zhang, Linfeng; Wang, Xin; Zheng, Congyi; Jiang, Linlin; Shao, Lan; Tian, Ye
Abstract : Objective: Understanding disparities in the burden of cardiovascular and all-cause mortality attributable to hypertension is crucial to inform and improve hypertension control measures. In this report, we estimate the population attributable fraction (PAF) of cardiovascular mortality attributable to hypertension at the national and provincial levels in China. Design and method: The multivariable-adjusted RRs by cox regression using cohort study with more than 30, 000 individuals, along with the national BP level from national study, were used to calculate the population attributable fractions (PAF). China Hypertension Survey, involving 458, 273 participants from 262 selected counties by stratified multistage random sampling method was used to calculate the prevalence of different BP level. CVD events were defined as the incidence of fatal and non-fatal stroke, fatal and non-fatal coronary heart disease (CHD), heart failure, and other causes from CVD. Results: Of more than 30, 000 individuals aged 35 years or older in the current study, over a mean of 4.8 years of follow up (143, 314.6 person-years), we documented 571 cardiovascular events. Comparing with normal BP, prehypertension and hypertension increased more than 50% and 170% risk for CVD events. Nationally, the CVD events attributable to prehypertension, hypertension and elevated BP were 17.30%, 28.74% and 37.99%, respectively. The PAFs for elevated BP ranged from 44.06% in Tianjin to 31.59% in Qinghai, however. In 2016, about 687.68 thousand (95%CI: 670.89, 705.15) and 1.14 (95%CI: 1.11, 1.17) million cardiovascular deaths were derived from prehypertension and hypertension, respectively. The province with high socio-demographic Index (SDI), such as Shanghai, Beijing and Tianjin, all had relative lower CVD death numbers for hypertension, with less than 15 thousands CVD deaths attributable to hypertension. More than 17 thousands CVD deaths could been derived from controlled hypertension in Shandong, Henna and Hebei provinces. Conclusions: Elevated BP were related with excess CVD deaths. Geography heterogeneity exited among 31 provinces, with lower excess CVD deaths in high SDI provinces. Additional attention should be taken to reduce prehypertension, which are preferable to attend universal health.